2019
DOI: 10.5114/ait.2019.91189
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life management in intensive care units: a multicentre observational prospective cohort study

Abstract: With the impressive improvements in medical care in recent years, it is to be expected that intensive care unit (ICU) care would result (as well as reducing mortality from serious critical illnesses) in increased comfort and dignity for patients and their families, thus reducing their suffering. However, the latter objective is still far from a reality, and the practice of applying futile support therapies is still common in the ICU setting, particularly among patients who eventually die in the hospital [1]. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The higher mortality in Polish ICUs compared with other European countries [25], which has been under debate in recent years, is rather due to differences in patient populations, indications for ICU admission, the availability of ICU beds and the organization of end-of-life care in Poland. This is also due to the skeptical attitude of some practitioners regarding guidelines on futile therapy [26,27] and official ICU admission criteria [28]. Although patients admitted to Polish ICUs are more often at higher risk of death compared with other countries, ICU mortality observed in the Silesian Registry of Intensive Care Units was lower than that predicted by the APACHE II score [29].…”
Section: Discussionmentioning
confidence: 99%
“…The higher mortality in Polish ICUs compared with other European countries [25], which has been under debate in recent years, is rather due to differences in patient populations, indications for ICU admission, the availability of ICU beds and the organization of end-of-life care in Poland. This is also due to the skeptical attitude of some practitioners regarding guidelines on futile therapy [26,27] and official ICU admission criteria [28]. Although patients admitted to Polish ICUs are more often at higher risk of death compared with other countries, ICU mortality observed in the Silesian Registry of Intensive Care Units was lower than that predicted by the APACHE II score [29].…”
Section: Discussionmentioning
confidence: 99%
“…This problem does not only concern Poland. It has been recently shown that adequate palliative care may be introduced with great heterogeneity and delay in other countries as well [ 39 ]. As a result, many patients with severe DoC remain in the ICU and are sometimes actively treated.…”
Section: Discussionmentioning
confidence: 99%
“…The higher mortality in Polish ICUs compared with other European countries (25), which has been under debate in recent years, is rather due to differences in patient populations, indications for ICU admission, the availability of ICU beds and the organization of end-of-life care in Poland. This is also due to the skeptical attitude of some practitioners regarding guidelines on futile therapy (26,27) (30). The cause of this phenomenon appears to be complex, and may result from substantial differences between the patient population in our unit (mixed admissions, including post-operative cases as the rst priority) and the target populations these prognostic models were developed for.…”
Section: Discussionmentioning
confidence: 99%